Pancreatic hepatoid adenocarcinoma with neuroendocrine differentiation and elevated AFP: a case report - Yang, Zhouliang; Li, Ting; Zhang, Xiaowei (Frontiers in Oncology, 2025)
BackgroundHepatoid adenocarcinoma (HAC) of the pancreas is a rare malignant tumor characterized by morphologic and immunophenotypic features resembling hepatocellular carcinoma. The tumor cells exhibit polygonal morphology with eosinophilic or clear cytoplasm and large, irregular nuclei. Immunophenotypically, the tumor cells are positive for alpha-fetoprotein (AFP) and glypican-3. Pancreatic HAC is rare, and neuroendocrine differentiation often complicates both diagnosis and treatment.Case descriptionWe report a case of pancreatic HAC with neuroendocrine differentiation and elevated AFP levels. A 46-year-old man was hospitalized due to progressive jaundice and dark urine that persisted for a week. Physical examination revealed bile duct dilation, a pancreatic head mass, and markedly increased AFP levels. The patient, with a history of schizophrenia and lung cancer surgery 2 years prior, was on regular medication. Following a pancreaticoduodenectomy, postoperative monitoring indicated normalization of AFP levels.ConclusionElevated serum AFP levels may be a crucial indicator for preoperative pancreatic HAC diagnosis. Additionally, pancreatic HAC has unique histological and immunophenotypic characteristics. However, neuroendocrine differentiation complicates diagnosis and treatment. Therefore, complete surgical resection is the optimal treatment option for this condition.